ChemInform Abstract: A Sustainable Approach for Lignin Valorization by Heterogeneous Photocatalysis. Issue 13 (March 2016) - Li, Shao‐Hai; Liu, Siqi; Colmenares, Juan Carlos; Xu, Yi‐Jun
Abstract: Review: [104 refs.